PENDAMPINGAN PENGGUNAAN BRANDING UNTUK SOCIAL MEDIA MARKETING BAGI PELAKU UMKM KOTA PATI - Teguh Setiadi; Eka Satria Wibawa; Bagus Sudirman; Aris Wijayanti (Buletin Abdi Masyarakat, 2024)
Business actors who fall under the criteria for Micro, Small and Medium Enterprises (MSMEs) from Langse Margorejo Pati Village still do not have clear branding and digital marketing due to various obstacles in promoting to online media. Even though this business has had a good impact on the surrounding environment. Having a logo that is still considered outdated and less attractive is also a major factor that prevents this business from growing rapidly. Surveys, interviews, discussions and implementation are used in this community service activity. The results of this activity are the creation of an attractive new logo, new packaging and the creation of social media accounts as well as assistance with branding and digital marketing, providing outreach materials so that small and medium business actors in Langse Margorejo Pati Village have a new understanding of this MSME digital promotion because they have been able to apply it. Online promotion with social media is a necessity. Keywords: Social Media, MSMEs, Branding, Digital Marketing